Інтегральна оцінка розвитку регіонів за сукупністю еколого-соціально-економічних показників моніторингу - Саричева, Л.В.; Кожевніков, А.В.; Рибко, В.В. (Міжнародний науково-навчальний центр інформаційних технологій і систем НАН та МОН України, 2010)
The problem of complex estimation of regions development based on values of ecologic-socioeconomic monitoring indicators set is considered. Definition models of integrated estimation of regions development, based on correlation, factor, cluster, and geoinformation analysis of indicators are described.